Studi Evaluatif Pengelolaan Limbah B3 Medis Padat di Puskesmas Kecamatan Gunungpati Kota Semarang - Adinda Rizqita Putri; Amnan Haris; Abdul Jabbar (Badan Riset dan Inovasi Daerah Kota Semarang, 2026)
Solid hazardous medical waste (B3 waste) is a hazardous byproduct that requires special handling according to applicable regulations. This study aims to evaluate the management of solid B3 medical waste in two Community Health Centers (Puskesmas) in Gunungpati Regency, namely Sekaran Community Health Center and Gunungpati Community Health Center. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The results of the study indicate that the management of solid B3 medical waste in both community health centers has not fully complied with the standards stipulated in the Regulation of the Minister of Health of Indonesia Number 2 of 2023. Sekaran Community Health Center faces challenges such as the lack of fire extinguishers (APAR) in the temporary storage facility, while Gunungpati Community Health Center lacks adequate internal transportation such as trolleys. In addition, there is a striking difference in the volume of solid B3 medical waste generated between inpatient and non-inpatient facilities. In 2024, Gunungpati Community Health Center generated the highest amount in September at 217.95 kg, while in Sekaran Community Health Center the highest amount was in June at 84.79 kg. Gunungpati Community Health Center produces a higher volume of waste due to its inpatient services and diverse health programs. These findings highlight the need for infrastructure strengthening, staff training, and regular evaluation to support the safe and sustainable management of hazardous solid medical waste at the primary healthcare level.